1995
DOI: 10.1016/1074-7613(95)90157-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal B lymphocyte delevopment, activation, and differentiation in mice that lack or overexpress the CD19 signal transduction molecule

Abstract: CD19-deficient mice were generated to examine the role of CD19 in B cell growth regulation in vivo. Deletion of CD19 had no deleterious effects on the generation of B cells in the bone marrow, but there was a significant reduction in the number of B cells in peripheral lymphoid tissues. B cells from CD19-deficient mice exhibited markedly decreased proliferative responses to mitogens, and serum immunoglobulin levels were also significantly decreased. In contrast, mice that overexpressed CD19 had significant def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
422
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(453 citation statements)
references
References 52 publications
22
422
1
Order By: Relevance
“…CD19 −/− mice exhibit three striking deficiencies in peripheral B‐cell subsets: ( i ) B‐1 cells, ( ii ) MZ B cells and ( iii ) GC B cells 12, 32, 33. We showed here that CD19 deficiency reduced MZ and FO B cells but not MZP (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…CD19 −/− mice exhibit three striking deficiencies in peripheral B‐cell subsets: ( i ) B‐1 cells, ( ii ) MZ B cells and ( iii ) GC B cells 12, 32, 33. We showed here that CD19 deficiency reduced MZ and FO B cells but not MZP (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…This suggested that signals delivered via CD19 are protective in hCR2 high mice during this stage of B cell development. The B cell populations in the CD19 − / − mice are largely unaltered in the bone marrow environment but a marked loss of B cell numbers is noted in the periphery, approximately at the point of sIgD and mCR1/2 expression (Engel et al, 1995;Rickert et al, 1995;Sato et al, 1995). Thus, it appeared possible that the point of endogenous mCR1/CR2 expression was linked to a negative effect on B cell numbers in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…From the moment it is expressed, CD19 has been shown to have regulatory function in the B cell (in pre-BCR signaling (Krop et al, 1996) and recombinase gene expression in pro-B cells (Billips et al, 1995)). However, absence of CD19 does not appear to influence B cell numbers until after B cells leave the bone marrow, where CD19 −/− mice show marked decrease in B cell numbers and significant defects in B cell development (Engel et al, 1995;Rickert et al, 1995;Sato et al, 1995). On the other hand, transgenic mice that over express human CD19 are hyperresponsive to transmembrane signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD19 is a co--signaling molecule for CR2 and ampliBies signaling from the BCR. The presence of CD19 on the cell surface is essential for B lymphocyte activation; under--expression of CD19 is associated with fewer peritoneal B cells, decreased B cell proliferative responses to mitogen, greatly reduced concentrations of serum immunoglobulin (Engel et al, 1995), decreased responses to T--cell--dependent B cell antigens, absent germinal center formation and afBinity maturation (Rickert et al, 1995). CD19 provides tonic survival signals to recirculating naive B lymphocytes; the B cell compartment in CD19 --/--mice can be partially rescued by over--expression of apoptosis survival genes (Otero et al, 2003).…”
Section: Cd19 -The Co-signaling Molecule Of Cr2mentioning
confidence: 99%